Does Access to Finance Matter in Microenterprise Growth? Evidence from Bangladesh - Khandker, Shahidur R. (World Bank, Washington, DC, 2013)
In less-developed economies such as Bangladesh, the farm sector is the major source of employment and income, while the rural nonfarm sector provides as an additional source of income. But the rural nonfarm sector increasingly plays an important role in fostering the development of the rural economy. A significant share of this sector is made up of microenterprise activities, which requires investment and access to adequate funds. This paper investigates the role access to finance plays in promoting the efficiency and growth of microenterprise activities. The findings suggest that households engaged in microenterprise activities, in addition to farm and other nonfarm activities, are much better off (in terms of income, expenditure and poverty) than those not engaged in such activities. Fewer than 10 percent of the enterprises have access to institutional finance (formal banks or microcredit), although the rate of return on microenterprise investments is more than sufficient (36 percent per year) to repay institutional loans. The research suggests that credit constraints may reduce the enterprises' profit margin by as much as 13.6 percent per year. As the returns to microenterprise investment are found to be high, microfinance institutions can play a larger role in supporting microenterprise growth in Bangladesh.